Effect of extraction solution on functional properties of extracted protein from Bombay locust (Patanga succincta Johannson, 1763) - Yuporn Puechkamutr; Supeeraya Arsa (My University, 2023)
Alternative sources of protein are gaining popularity since they require less natural resource input, but still provide a significant amount of protein as compared to traditional protein sources. Insect protein is one of the alternative protein types, and due to its nutritional benefits, research interest in Bombay locust (Patanga succincta) (BL) protein has grown. In the present work, we aimed to determine the protein content, yield, molecular weight profile, and functional properties such as protein solubility, emulsion, and foam properties of BL protein extracted using distilled water, salt (NaCl), or alkaline (NaOH) solution, at the concentrations of 0.5, 1.0, or 1.5%. The highest protein extraction yield was alkaline soluble protein (22 - 28%), which was followed by water (16%) and salt (11 - 13%) soluble proteins. The protein powder prepared by 0.5% alkaline extraction had the highest foam capacity (33.33%) and foam stability (12.50%) (p < 0.05), but the water soluble protein powder had the highest emulsion activity index (118.3 m2/g) and emulsion stability index (52.45 min) (p < 0.05). These results indicated that the type and concentration of solution could have an impact on the protein extraction yield, molecular weight profile, and functional characteristics.
Keywords: Distilled water; Protein purification; Water extraction; Insect Utilization and Effects